2004
DOI: 10.1590/s1415-47572004000400019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RAPD, RFLP, AFLP and SSR markers for diversity studies in tropical maize inbred lines

Abstract: In order to compare their relative efficiencies as markers and to find the most suitable marker for maize diversity studies we evaluated 18 tropical maize inbred lines using a number of different loci as markers. The loci used were: 774 amplified fragment length polymorphisms (AFLPs); 262 random amplified polymorphic DNAs (RAPDs); 185 restriction fragment length polymorphisms (RFLPs); and 68 simple sequence repeats (SSRs). For estimating genetic distance the AFLP and RFLP markers gave the most correlated resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
128
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(161 citation statements)
references
References 34 publications
18
128
0
8
Order By: Relevance
“…However, correlation between RAPD and the other markers was low (0.71). Garcia et al (2004) found similar results in maize (Zea mays L.).…”
Section: Comparison Of the Four Marker Systems In Cynodon Genetic Anasupporting
confidence: 66%
See 1 more Smart Citation
“…However, correlation between RAPD and the other markers was low (0.71). Garcia et al (2004) found similar results in maize (Zea mays L.).…”
Section: Comparison Of the Four Marker Systems In Cynodon Genetic Anasupporting
confidence: 66%
“…The PCR-based DNA markers, such as RAPD and amplified fragment length polymorphism have been used in studies of genetic diversity, relatedness, phylogeny, and in identifying offtypes in cultivars of Cynodon (Vos et al 1995;CaetanoAnolles et al 1995;Zhang et al 1999;Karaca et al 2002;Garcia et al 2004;Wu et al 2005). While these studies provide baseline information on the variation in diversity, ploidy level and geographical distribution, more information on relationships between polyploidy and genetic diversity is needed to clarify evolution and relationships among Cynodon accessions with ploidy series.…”
Section: Introductionmentioning
confidence: 99%
“…Percent Disagreement Values (PDVs) distance matrix, tree clustering diagram and neighbor-joining stars are different statistical techniques to determine the extent of genetic diversity. Polymorphism Information Content (PIC) is another statistical technique that can be deployed to evaluate the polymorphism acquired through different techniques, primers or markers [35][36][37][38].…”
Section: Genetic Diversity In Cottonmentioning
confidence: 99%
“…RAPD markers are a widely used in the genetic evaluation because they use small amounts of DNA to identify variations between plants at the DNA level and do not require information of the genome of interest. RAPD applications in plant breeding consist genetic mapping, Marker Assisted Selection (MAS) and transfer of useful genes and germplasm evaluation (Boonparkob, 1996;Garcia et al, 2004). RAPD marker is based on DNA amplification by non-specific primers and uses the polymerase chain reaction.…”
Section: Introductionmentioning
confidence: 99%